Ground-truthing the planktic foraminifer-bound nitrogen isotope paleo-proxy in the Sargasso Sea. (15th August 2018) - Smart, Sandi M.; Ren, Haojia; Fawcett, Sarah E.; Schiebel, Ralf; Conte, Maureen; Rafter, Patrick A.; Ellis, Karen K.; Weigand, Mira A.; Oleynik, Sergey; Haug, Gerald H.; Sigman, Daniel M.
Abstract: We report the nitrogen (N) isotope ratios (δ 15 N) of planktic foraminifera collected from upper-ocean net tows (surface to 200 m), moored sediment traps, and core-top sediments at the Bermuda Time-series Site in the northern Sargasso Sea between 2009 and 2013. Consistent with previous measurements from low-latitude core-top sediments, the annually-averaged δ 15 N of organic matter bound within the shells of euphotic zone-dwelling, dinoflagellate symbiont-bearing foraminifera collected in net tows (2.3‰ on average) approximates that of shallow thermocline (∼200 m) nitrate (2.6‰), the dominant source of new N to Sargasso Sea surface waters. Deeper-dwelling foraminifer species without dinoflagellate symbionts tend to have a higher δ 15 N (3.6‰ on average). We observe no systematic difference between the bulk tissue and shell-bound δ 15 N in net tow-collected foraminifera. A decline in shell N content is observed from net tows (6.8 nmol/mg) to sediment traps (5.4 nmol/mg) and surface sediment (3.0 nmol/mg). On average, shell-bound δ 15 N rises from net tows (3.1‰) to sediment traps (3.7‰) but does not change further upon incorporation into the sediments (3.7‰). Together, these observations are consistent with preferential loss of shells or shell portions with lower δ 15 N and higher N content during sinking through the upper 500 m, followed by a non-isotope fractionating decrease in N content between sinking and burial. Time-series data from sediment traps (and to a lesser extent, surface net tows) exhibit seasonal δ 15 N variations, with a minimum in early spring, a maximum in late spring and a decline from summer to fall. These variations appear to arise from seasonal changes in the δ 15 N of total upper-ocean biomass, which are, in turn, driven by early springtime nitrate supply, subsequent nitrate drawdown, and an increase in the relative importance of ammonium recycling into the late summer and early fall. The δ 15 N connection between total upper ocean biomass and foraminifera indicates that foraminifer-bound δ 15 N records the δ 15 N of the annual nitrate supply in oligotrophic (e.g., subtropical) environments but will also be sensitive to the degree of nitrate consumption in high-nutrient regions and possibly to changes in upper-ocean ammonium recycling under some conditions.